Antifungal Activities of Essential Oils and Crude Extracts of Some Aromatic Plants Against Fusarium Rot of Trichosanthes dioica - Wagle, Bina; Budathoki, Usha (Nepal Journal of Science and Technology, 2013)
This experiment was conducted for assessing the antifungal activities of essential oils and crude extracts of some aromatic plants against Fusarium rot of Trichosanthes dioica was at the Central Department of Botany. Pathogenicity test was taken for the confirmation of disease by transferring the inoculum from pure culture. For the control of the above fungus essential oils and extracts of five aromatic plants Zanthoxylum armatum, Mentha arvensis, Amomum subulatum, Valeriana jatamansi and Cymbopogon flexuosus were used. Each oil and extracts were diluted in different concentration in 80% acetone and in distilled water respectively. The value of minimum inhibitory concentration and percentage of mycelia growth inhibition of oil and extracts were obtained as, oil of C. flexuosus showed the higest fungitoxicity (100%) at the 5.0 and 50 ?lml-1 concentration followed by Z. armatum, M. arvensis, A. subulatum and V. jatamansi were found to be 10 and 100 ?lml-1 respectively also the higest percentage of mycelial growth inhibitors were found to be C. flexuosus followed by A. subulatum, Z. armatum, M. arvensis and V. jatamansi . Similarly extracts of C. flexuosus followed by Z. armatum, A. subulatum, V. jatamansi and M .arvensis respectively. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 97-102 DOI: http://dx.doi.org/10.3126/njst.v13i2.7720